On-farm characterization and present status of North Bengal Grey (NBG) cattle in Bangladesh - Al-Amin, M; Nahar, A.; Bhuiyan, A.K.F.H.; Faruque, M.O. (Cambridge University Press, 2007)
North Bengal Grey (NBG) cattle are an important indigenous cattle genetic resource found mainly in the northern part of Bangladesh. The study was undertaken at Bogra district. The physical and morphological characteristics, and Kahalu Upazila (sub-district) in the Bogra district. The physical and morphological characteristics, and the productive and reproductive performance of NBG cattle were studied. The coat colour of these neck regions in adults bulls was found to be generally ashy with a range of shades. The body is small, compact and less fleshy. Ear length and ear width were 18.0±0.17 and 11.0±0.21 cm, respectively. The head length average was 38.0±0.56 cm, the head width 16.0±17cm, foreleng length average 65.0±0.64 cm, the hind leg length 71.0±0.64cm, the tail length average 71.0±0.67 cm, the horn length average 9.0±0.39 cm, the horn diameter 10.0±0.37 cm, the average teat length 5.0±0.18cm, the teat diameter 6.0±0.22 cm, the distance between the front teats 7.0±0.13 cm and distance between the rear teats 7.0±0.13 cm. Body length, height at wither and heart girth in adult cows were 105.0±1.20, 94.0±1.12 and 127.0±1.52 cm, respectively. The recorded highest peak milk production per day was 3.5±0.18 kg, lactation length was 219±6.1 days, and the dry period was 180 ± 6.8 days. The average birth weight calves was 180±6.8 days. The average birth weight of calves was 18.4±0.52kg and mature live weight of cows 241.0±4.0kg. The calving 1191±19.7 days, gestation length 281±1.3 days, calving interval 442±7.4 days, postpartum heat period 110±4.2 day sand the number of services per conception 1.4 ±0.6. About 54%of total cattle population was NBG cattle in the surveyed area of Bangladesh. The results indicated that the productivity and reproductively performance of NBG cattle was better than other non-descript indigenous cattle of Bangladesh. The study further revealed an obvious need for more in-depth and objective information on wider samples of this type of indigenous cattle in order to assess the future need for conservation and improvement programs to be undertaken.